Two-stage iterative data transmission scheduling algorithm for satellite Internet integrating communication and remote sensing - LI Hai; LI Yongjun; ZHANG Taijiang; LI Yu; ZHAO Shanghong; WANG Jie; HAN Yue (Tongxin xuebao)
Aiming at the data transmission scheduling problem in the satellite Internet integrating communication and remote sensing (SatInternet-CR), a mathematical model with the goal of maximizing data transmission profits was established subject to constraints including data transmission windows and satellite energy consumption. Differentiated data transmission task demands, various ground receiving resources including direct satellite communication terminals, and remote sensing data inter satellite offloading, etc, were considered by the established mathematical model. Due to the large scale of variables and coupling of constraints, it was difficult to directly solve it. Therefore, a two-stage iterative data transmission scheduling (TSIDTS) algorithm based on the divide and conquer strategy was proposed. In the first stage, delay sensitive data transmission tasks were scheduled using dynamic neighborhood search algorithms. In the second stage, a greedy adaptive large neighborhood search algorithm was proposed to allocate data transmission resources for delay tolerant data transmission tasks. In the two-stage iterative optimization process, the Metropolis criterion was introduced to improve the global search capability. Simulation results demonstrate that the proposed TSIDTS algorithm significantly improves data transmission profits compared with the same type data transmission scheduling algorithms, and confirm that the inter-satellite communication link can significantly improve the timeliness of remote sensing data downloading.